Performance analysis on high -speed network for secure big data streaming of detecting VoIP calls - E, Rajinikanth; S, Jayashri (International Journal of Engineering and Technology, 2019)
In this fast growing world, Internet-based Call transferring facilities are most popular and all the telecommunication industries are showing more interest in developing interesting key features and providing better solutions to the users. The detection of transmission and monitoring voice data causes lots of security issues and results in lacking over users to use the VoIP messages instead, of voice calls without an internet. Although there are many VoIP detecting techniques, they are not accurate and not efficient. This can be resolved by using AES algorithm which helps to transfer media files from one end to another end securely. In this approach, Big Data schemes are handled because of media-oriented handlings. This entire system deals with successful and intelligent communication over Internet-based Voice Call transmission. Some of the parameters used are transmission bit rate, speed, packet size, and intervals. Intelligent Media Packet transfer scheme is used for network analysis and route establishment. The proposed system outperforms the graphical representation of throughput, delay, and packet transmission speed. The main objective of this system is to efficiently process high-speed real-time network traffic, which proves that our approach of Intelligent Media Transfer (IMT) outperforms the existing systems with the ability to work in real-time and high-speed Big Data environment.Â